PENGENALAN PERANCANGAN JEMBATAN KONEKSI BANGUNAN PADA PLAZA UTAMA AL-AMIN LIVING LAB DAN INDUSTRIAL PARK DI DESA SAMPE CITA KECAMATAN KUTALIMBARU - Dara Wisdianti; Novalinda, Novalinda; Faurantia Forlana Sigit; Siregar, Ida Khairani (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2024)
The design of building connection bridges in the main plaza is a crucial step in the development of urban infrastructure that allows pedestrians to move conveniently and efficiently between various important points in an area. This study aims to determine the design of building connection bridges in the main plaza of Al-Amin Living Lab and Industrial Park in Sampe Cita Village, Kutalimbaru District will function for pedestrians. The material of this research is the location of the site in Sampe cita Village, Kutalimbaru District, Deli Serdang Regency with the parameters observed are the physical conditions of the design location and non-physical conditions. The results of this study explain that the Facilities and Infrastructure of the Al Amin Living Lab and Industrial Park Mixed Use Building Connection Bridge consists of circulation connecting the Mixed Use building and Viewing Deck and the design direction of the Al Amin Living Lab and Industrial Park Mixed Use Building has met the criteria.